On The Modelling of Jet Grouting For Deep Excavation Analysis - Assessing the Suitability of Shotcrete Material Model for Field Applications - Tran, David; Armediaz, Yohanes (My University, 2021)
Retaining wall is a common solution to secure excavations and to minimise surrounding ground settlements, jet grouting is implemented. Currently, jet grouting structures are commonly numerically modelled with Mohr-Coulomb model which is a linear elastic and perfectly plastic model. However, in actuality, jet grouting behaves non-linearly. An alternative approach is to utilize a new novel material model, Shotcrete, originally created for tunnel linings. However, utilising Shotcrete for jet grouted retaining walls had rarely been done and not much research has been con ducted. In this thesis, the two material models for a jet grouted retaining columns were compared. The practicality of Shotcrete model in the industry is also explored. The study is based on an actual excavation project in Oslo, Norway. Model parameters were derived from the original geotechnical investigation, new laboratory tests and literature values. The results show that both models predict similar deformations. The similarity can be explained by the fact that the columns are still in the elastic region, where Shotcrete model adopts Mohr-Coulomb failure criteria similar to Mohr-Coulomb model. Additionally, deformations can be caused by other factors in the system, which are the same in the two models. Furthermore, combination of the original geotechnical investigation and additional laboratory tests were insufficient to derive the necessary model parameters for the model. Instead, literature values were used which may not be suitable for jet grouting materials. In conclusion, the study have shown that there is not enough merit to implement Shotcrete model over Mohr-Coulomb model.
Keywords: material model; deep excavation; Plaxis 2D; Shotcrete; Mohr-Coulomb; retaining wall; jet grouting